Interview with Argha Manna. Issue 2 (1st November 2020) - Bhattacharjee, Partha; Tripathi, Priyanka
Argha Manna is a cancer-researcher-turned cartoonist. He worked as a research fellow at Bose Institute, India. After leaving academic research, he joined a media-house and started operating as an independent comics artist. He loves to tell stories from the history of science, social history and lab-based science through visual narratives. His blog, Drawing History of Science (https://drawinghistoryofscience.wordpress.com ), has been featured by Nature India. Argha has been collaborating with various scientific institutes and science communicator groups from India and abroad. His collaborators are from National Centre for Biological Science (NCBS, Bangalore), Centre for Cellular and Molecular Biology (CCMB, Hyderabad), Jadavpur University (Kolkata), Heidelberg Center for Transcultural Studies (University of Heidelberg, Germany) and a few others. Last year, he received STEMPeers Fellowship for creating comics on the history of vaccination and other aspects of medical histories, published in Club SciWri, a digital publication wing of STEMPeers Group. Currently, Argha is collaborating in a project, 'Famine Tales from India and Britain' as a graphic artist. This is a UK-based project, funded by the Arts and Humanities Research Council, led by Dr Ayesha Mukherjee, University of Exeter. In this interview, Partha Bhattacharjee and Priyanka Tripathi speak with Indian 'alternative' cartoonist Argha Manna to trace his journey from a cancer researcher to a cartoonist. Manna is a storyteller of history of science, in visuals. Recently, his works reflect social problems under the light of historical and scientific theories. Bhattacharjee and Tripathi trace Manna's shift from a science-storyteller in a visual medium to a medical-cartoonist who is working on issues related to a global pandemic, its impact on life and literature vis-à-vis social intervention. They also focus on Manna's latest comics on COVID-19.